Determination of Surface Water Quality Parameters of Sakarya River, Turkey - Yerel, Suheyla (Asian Journal of Chemistry, 2010)
This study aims to investigate the changes of the surface water quality parameters on the Sakarya river in Turkey. For this purpose water quality samples were collected from 5 monitoring stations in the river. Variations in the surface water quality parameters of the monitoring stations have been examined by environmetric methods including ordinal logistic regression technique and cluster analysis. Ordinal logistic regression results showed that TDS, SO4 and NO3-N were identified as the water quality parameters that displayed essential variations. The cluster analysis of the monitoring stations determined two clusters. It was concluded that agricultural pollution affected the southeast part of the river. These methods are believed to help to water quality issues.